Effective strategy for polymer synthesis: multicomponent reactions and click polymerization. (September 2022) - Wang, Chang; Yu, Bing; Li, Wenlong; Zou, Wentao; Cong, Hailin; Shen, Youqing
Abstract: The rational selection of organic reactions in polymer synthesis is an important research content of polymer science. In recent years, multicomponent reaction as an efficient and green synthesis method has attracted the wide attention of researchers, injecting new and powerful vitality into the field of polymer synthesis. In the study of multicomponent reaction, researchers found the intersection of multicomponent reaction and click chemistry and put forward the concept of Multicomponent Click Reaction (MCR-Click), which is a kind of Multicomponent Reaction with high activity, atomic economy, and some green chemical properties. The application of MCR in polymer chemistry is reviewed in this paper. It is expected that this reaction will arouse the attention of polymer chemists and play a new role in polymer science. Highlights: Research progress of reactions such as Ugi, Passerini, Biginelli, etc. High-yield polymer synthesis route and structure. Effective means of polymer modification. Achievements of multicomponent click reactions in the field of biomedicine.